Cataclysmic variables based on the stellar spectral survey LAMOST DR3. (June 2018) - Han, Xianming L.; Zhang, Li-Yun; Shi, Jian-Rong; Pi, Qing-Feng; Lu, Hong-Peng; Zhao, Li-Bo; Terheide, Rachel K.; Jiang, Lin-Yang
Abstract: Big data in the form of stellar spectra from the spectroscopic survey associated with the Large Sky Area Multi-object Fiber Spectroscopic Telescope (LAMOST) are important for studying properties of cataclysmic variables (CVs). By cross matching the catalogs of CVs compiled with LAMOST DR3, acquired from October 2011 to July 2015, we obtained the first spectroscopic catalog for CVs observed by LAMOST with high signal to noise ratio, above 8. By integrating line profiles, their equivalent widths (EWs) of the H α, H β, H γ and H δ, as well as He I 5876 and 6678 Å lines, were calculated. There were 74 stellar spectra from 48 known CVs and three spectra from three new CV candidates. At the same time, we also collected their previously published EWs. Thirty-three objects had repeated spectra and 30 stars showed spectral variability in the H α line. Moreover, we carried out photometric follow-up studies for five CVs (UU Aqr, TT Tri, PX And, BP Lyn and RW Tri). We obtained nine new light curves and revised their linear ephemerides. For RW Tri, there is a possible oscillation with an amplitude of 0.0031(2) days and a period of 47.6 ± 0.4 years, which might be caused by a third body (brown dwarf) or magnetic activity cycle.